Cavity as a Source of Conformational Fluctuation and High-Energy State: High-Pressure NMR Study of a Cavity-Enlarged Mutant of T4Lysozyme - Maeno, Akihiro (Biophys J, 2015)
Although the structure, function, conformational dynamics, and controlled thermodynamics of proteins are manifested by their corresponding amino acid sequences, the natural rules for molecular design and their corresponding interplay remain obscure. In this study, we focused on the role of internal cavities of proteins in conformational dynamics. We investigated the pressure-induced responses from the cavity-enlarged L99A mutant of T4 lysozyme, using high-pressure NMR spectroscopy. The signal intensities of the methyl groups in the (1)H/(13)C heteronuclear single quantum correlation spectra, particularly those around the enlarged cavity, decreased with the increasing pressure, and disappeared at 200 MPa, without the appearance of new resonances, thus indicating the presence of heterogeneous conformations around the cavity within the ground state ensemble. Above 200 MPa, the signal intensities of >20 methyl groups gradually decreased with the increasing pressure, without the appearance of new resonances. Interestingly, these residues closely matched those sensing a large conformational change between the ground- and high-energy states, at atmospheric pressure. (13)C and (1)H NMR line-shape simulations showed that the pressure-induced loss in the peak intensity could be explained by the increase in the high-energy state population. In this high-energy state, the aromatic side chain of F114 gets flipped into the enlarged cavity. The accommodation of the phenylalanine ring into the efficiently packed cavity may decrease the partial molar volume of the high-energy state, relative to the ground state. We suggest that the enlarged cavity is involved in the conformational transition to high-energy states and in the volume fluctuation of the ground state.